The mosaic genome structure and phylogeny of Shiga toxin-producing Escherichia coli O104:H4 is driven by short-term adaptation. (May 2015) - Zhou, K.; Ferdous, M.; de Boer, R.F.; Kooistra-Smid, A.M.D.; Grundmann, H.; Friedrich, A.W.; Rossen, J.W.A.
Abstract: Shiga toxin-producing Escherichia coli (STEC) O104:H4 emerged as an important pathogen when it caused a large outbreak in Germany in 2011. Little is known about the evolutionary history and genomic diversity of the bacterium. The current communication describes a comprehensive analysis of STEC O104:H4 genomes from the 2011 outbreak and other non-outbreak-related isolates. Outbreak-related isolates formed a tight cluster that shared a monophyletic relation with two non-outbreak clusters, suggesting that all three clusters originated from a common ancestor. Eight single nucleotide polymorphisms, seven of which were non-synonymous, distinguished outbreak from non-outbreak isolates. Lineage-specific markers indicated that recent partitions were driven by selective pressures associated with niche adaptation. Based on the results, an evolutionary model for STEC O104:H4 is proposed. Our analysis provides the evolutionary context at population level and describes the emergence of clones with novel properties, which is necessary for developing comprehensive approaches to early warning and control.